Development and Population Growth Rates of Sitophilus zeamais (Coleoptera: Curculionidae) Exposed to a Sublethal Concentration of Essential Oil of Piper hispidinervum - Lucas Martins Lopes; Lêda Rita D’Antonino Faroni; Gutierres Nelson Silva; Douglas Rafael e Silva Barbosa; Marcela Silva Carvalho; Herus Pablo Firmino Martins; Thaís Rodrigues dos Santos; Igor da Silva Dias; Adalberto Hipólito de Sousa (Insects, 2025)
Essential oils have emerged as promising alternatives for pest insect control. However, sublethal effects on insect reproduction and development are rarely explored, despite their relevance to integrated pest management (IPM). This study evaluated the sublethal effects of Piper hispidivervum C. DC. essential oil (EOPH) on the development and population growth of four populations of Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae), as well as the persistence of safrole residue in treated corn grains. Population development rates were determined using emergence curves and total emerged adults, while population growth was assessed by counting live insects in the feeding substrate at different storage intervals. Safrole residue persistence was analyzed using solid-phase microextraction in headspace mode (SPME-HS). Sublethal exposure to EOPH significantly reduced the development rate, total emergence, and growth in three of the four populations. The population from Crixás, GO, showed no significant reduction, with a population curve overlapping the control. The lethal dose was reduced by 98.20%, indicating low persistence and potential food safety. The EOPH exhibited sublethal effects on S. zeamais populations, reducing both development rates and population growth. This reduction varied among the populations studied. Further research is encouraged to explore its effects on different insect populations and under broader environmental conditions.